Simulation of Many‐Electron Systems That Exchange Matter with the Environment. Issue 10 (12th August 2018) - Delle Site, Luigi
Abstract: The computational treatment of many‐electron systems capable of exchanging electrons and nuclei with the environment represents one of the outermost frontiers in simulation methodology. The exchanging process occurs in a large variety of natural and artificially induced phenomena which are of major relevance to several leading fields of academic research and modern technology. In this Progress Report, an overview of problems in current materials science and chemical physics is presented where the corresponding computational approaches require the concept of an electronic system with open boundaries. Quantum and quantum/classical computational techniques treat the exchange of electrons with the environment at different computational efficiency, conceptual rigorousness, and numerical accuracy. The overall emerging picture shows a rich availability of interesting ideas, some with a higher weight on the pragmatic side, others with higher weight on the conceptual side; possible combinations, in perspective, may push the field much beyond its current frontiers. Abstract : Systems with open boundaries that exchange matter with the exterior are the most common in nature and technology . For theoreticians and simulators, the proper description of this exchange is a challenging task, in particular, for many‐electron systems. Here, relevant examples of theoretical methods and corresponding computational approaches for open many‐electron systems are discussed. Some possible directions of future development of the field are also proposed.